The impact of domestic and global factors on individual public, domestic and foreign bank performances in Türkiye - Serkan Çiçek; Aynur Yıldırım (Central Bank Review (CBR), 2024)
The Turkish economy has encountered significant shocks in interest rates and foreign exchange along with global risks in recent years. These shocks had an impact not only on the real sector but also on the banking sector's returns, depending on the ownership structure. This study examines the sensitivity of banking sector stock returns to the exchange rate, interest rate, and VIX index using data from January 4, 2005 to March 28, 2023. Using multivariate diagonal BEKK-GARCH methodology, the study found that (i) half of private banks experienced a mean spillover from the interest rate to their returns, but not from the exchange rate and VIX index, (ii) the returns of public banks, on the other hand, did not respond to any variable in the mean equations, (iii) the explanatory power of exchange rate and interest rate risks is higher than the power of the changes in these variables, (iv) the spillover of global risk in covariance equations is higher compared to exchange and interest rate risks, (v) the mean equations do not have an asymmetric structure, but the covariance equations exhibit structural breaks. These findings suggest that in the last decade, the interest rate policy has become the main variable affecting the stock returns in Türkiye, foreign exchange has become a safe haven due to this policy, and the relationship between the exchange rate and stocks that existed in the past has been disrupted.
Keywords: C32; G21; 330; Volatility spillover; Diagonal BEKK-GARCH; Interest rate risk; Foreign exchange risk